Genotype and risk of major bleeding during warfarin treatment. (December 2014) - Kawai, Vivian K; Cunningham, Andrew; Vear, Susan I; Van Driest, Sara L; Oginni, Abimbola; Xu, Hua; Jiang, Min; Li, Chun; Denny, Joshua C; Shaffer, Christian; Bowton, Erica; Gage, Brian F; et al.
Aim : To determine whether genetic variants associated with warfarin dose variability were associated with increased risk of major bleeding during warfarin therapy.Materials & methods : Using Vanderbilt's DNA biobank we compared the prevalence of CYP2C9, VKORC1 and CYP4F2 variants in 250 cases with major bleeding and 259 controls during warfarin therapy.Results : CYP2C9*3 was the only allele that differed significantly among cases (14.2%) and controls (7.8%; p = 0.022). In the 214 (85.6%) cases with a major bleed 30 or more days after warfarin initiation, CYP2C9*3 was the only variant associated with bleeding (adjusted odds ratio: 2.05; 95% CI: 1.04, 4.04).Conclusion : The CYP2C9*3 allele may double the risk of major bleeding among patients taking warfarin for 30 or more days.